Methane production potential of soil profile in organic paddy field - Mujiyo Mujiyo; Bambang Hendro Sunarminto; Eko Hanudin; Jaka Widada; Jauhari Syamsiyah (Soil and Water Research, 2017)
The use of organic fertilizers in the organic paddy/rice field can increase methane (CH4) production, which leads to environmental problems. In this study, we aimed to determine the CH4 production potential (CH4-PP) by a soil profile from samples using flood incubation. Soil properties (chemical, physical, and biological) were analyzed from soil samples of three different paddy farming systems (organic, semi-organic, and conventional), whilst soil from teak forest was used as the control. A significant relationship was determined between soil properties and CH4-PP. The average amount of CH4-PP in the organic rice field profile was the highest among all the samples (1.36 µg CH4/kg soil/day). However, the CH4 oxidation potential (CH4-OP) is high as well, as this was a chance of mitigation options should focus on increasing the methanotrophic activity which might reduce CH4 emissions to the atmosphere. The factor most influencing CH4-PP is soil C-organic (Corg). Corg and CH4-PP of the top soil of organic rice fields were 2.09% and 1.81 µg CH4/kg soil/day, respectively. As a consequence, here the mitigation options require more efforts than in the other farming systems. Soil with various amounts of Corg reached a maximum point of CH4-PP at various time after incubation (20, 15, and 10 days for the highest, medium, and the lowest amounts of Corg, respectively). A high amount of Corg provided enough C substrate for producing a higher amount of CH4 and reaching its longer peak production than the low amount of Corg. These findings also provide guidance that mitigation option reduces CH4 emissions from organic rice fields and leads to drainage every10-20 days before reaching the maximum CH4-PP.